CYSTOLITHIASIS IN A STERILE DOMESTIC MALE CAT - M Iqbalsyah Rudi; I Putu Gede Yudhi Arjentinia; Putu Devi Jayanti (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Urolithiasis is a condition where uroliths or crystals form excessively in the urinary tract, such as the kidneys, ureters, urinary bladder and urethra. Specifically, the presence of uroliths in the urinary bladder is called cystolithiasis. Risk factors for urolithiasis can include several aspects, namely urinary tract infections, feed, lack of drinking water intake, gender, race, age, and obesity factors. The case cat named Kiko with a domestic short hair breed, 3 years old, male with black and white hair and weighing 6 kg has had difficulty urinating since February 26, 2025. The results of the physical examination showed that the cat had dysuria, stranguria and hematuria. Ultrasonography examination found crystals in the urinary bladder and thickening of the mucosal wall of the urinary bladder. The results of the native and sedimentation examinations showed struvite crystals in the patient's urine. The results of the urine chemistry examination showed an increase in leukocytes and blood in the urine and a urine pH of 8.5. Treatment was carried out by installing a urinary catheter to flush the urinary bladder. Drug therapy given was by administering the antibiotic cefadroxil, the anti-inflammatory dexamethasone, and probiotics. To prevent the risk of this disease recurring, dietary changes were made by providing prescribe urinary feed.